Adult diet and exposure to semiochemicals influence male mating success in Ceratitis rosa (Diptera: Tephritidae). (28th June 2011) - Quilici, S.; Schmitt, C.; Vidal, J.; Franck, A.; Deguine, J. P.
Abstract: The Natal fruit fly, Ceratitis rosa (Diptera: Tephritidae), is a major pest of fruit crops in Reunion island. The sterile insect technique (SIT), which has frequently been used against some fruit fly species, could also contribute to the control of this pest. However, mass‐rearing procedures and irradiation can strongly reduce the mating competitiveness of males. In this study, we investigated the influence of two essential oils [ginger root oil (GRO) and orange oil (OO)] on the males of C. rosa, in terms of attractiveness and effect on mating success. The influence of adult food regime on mating success of the males was also studied. During tests in choice situation between the two oils, mature males were more attracted to GRO compared with OO. This was not the case when males had not reached their sexual maturity, which indicates that this attractiveness is age‐dependent. The addition of proteins to the adult diet increased the mating competitiveness of the males, compared with males fed with sugar only. Males fed with a 'full' diet (sugar and hydrolysed yeast) accounted for 85% of all matings compared with 15% for those fed with a sugar‐only diet. Results were similar for wild males and for males from a laboratory‐reared colony. Exposure of the males to both types of oils significantly increased the mating competitiveness of sugar‐fed males, while only the exposure to GRO was able to increase that of males previously fed with a 'full' diet. This study provides promising results for the improvement of male competitiveness in the perspective of SIT programmes against C. rosa in the future.